Orthodontic retention protocol among Kurdistan Region of Iraq orthodontists - Mahmoud Kanan Mohsin; Zana Qadir Omer; Rebin Ali Mohammed Amin (Erbil Dental Journal)
Background and Objectives: Retention is important stage of orthodontic treatment that preserves teeth in new positions. To make occlusion stable after orthodontic treatment, retention protocol is recommended. There is great variation among orthodontists regarding type, duration and strategies of retention following orthodontic treatment. Therefore, the aim of current survey was to identify the common retention procedures and to evaluate the results with similar studies conducted in different countries.